UPAYA PENINGKATAN PEMAHAMAN KONSEP SISWA PADA PEMBELAJARAN PERKAKAS TANGAN MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI SMKN 1 CILEUNGSI - Hadi Koeswara (Asosiasi Dosen Muda Indonesia, 2023)
The purpose of this study was to increase students' understanding of the concepts of class X TPGM at SMKN 1 Cileungsi through the problem-based learning model. The method used is Classroom Action Research (CAR) using the spiral/cycle model from Kemmis and McTaggart which consists of 2 cycles with four stages in each cycle namely, planning, action, observation and reflection. The subjects of this study were 36 students. Data collection techniques used include observation, learning achievement tests, and documentation. Data on student activity was obtained through class observation and analyzed to compare student activity levels in each cycle. Data about students' understanding of concepts can be seen from the learning outcomes obtained through written tests and practical tests then analyzed to compare the results of the exams in each cycle. The results showed an increase in activity and student learning outcomes in the subject of hand tools using the PBL method. This is evidenced by the increase in student activity as seen from the percentage of student activity in cycle I of 55.56% (enough) increased by 22.22% in cycle II to 77.78% (good). Of the 9 aspects observed in cycle I, 4 aspects are still below the KKM, namely in the aspect of the ability to work on student worksheets, the courage of students in presenting their findings, the ability of students to relate material to real life, and the ability to solve problems while in cycle II all aspects have reached KKM. An increase in students' understanding of concepts can be seen from the average increase in practical test scores and written test scores. The average practice test score in cycle I was 68.24 (55.56%) increasing to 81.59 (86.11%) in cycle II. While the average written test score in cycle I was 59.08 (41.67%) increased to 62.04 (77.78%) in cycle II of the 36 students who still had not reached the KKM on the practical test as many as 5 students (13 .89%) while in the written test there were 8 students (22.22%) at the end of the cycle.